Impact of Screen Time and Sleep Duration on Adults’ Body Mass Index in A University in Chengalpattu District – A Cross-Sectional Study - Nagarajan, Vaishnavi; Hussain, Aamina; Srinivasan, Abirami; Anantharaman VV; Saranya S (National Journal of Community Medicine, 2025)
Background: The rapid technological advancements of the 21st century have led to significant changes in lifestyle behaviors, particularly among young adults in university settings. One of the most prominent shifts has been the increase in screen time due to widespread access to digital devices. Sleep is mainly being compromised by screen time which can be either for work or for leisure activities. Excessive screen time and short sleep duration has raised concerns regarding its potential negative impact on physical health, particularly on Body Mass Index (BMI). The aim was to estimate the prevalence of under-weight, normal weight, over-weight and obese and to assess the effect of sleep duration and screen time on body mass index of the adults in a university in Chengalpattu district. Methodology: A descriptive cross-sectional study was conducted among staffs, students and workers from a Private university, Chengalpattu district, Tamil Nadu. Simple random sampling method was used and a sample size of 672 was calculated. Results: Of 672 respondents, majority were males 364 (54.2%) and 308 (45.8%) were females. Almost more than half were in the age group of 31 - 60 years (392, 58.3%). It was found that almost two-third (470, 69.9%) of the participants had screen time for <4 hours / day. A statistically significant association was found between age of the participants, their screen time and sleep time. Conclusions: The findings suggest that excessive screen time and insufficient sleep are significantly associated with higher BMI, highlighting the importance of addressing these modifiable behaviors to combat the growing prevalence of obesity among university students.